Production of cellulose nanofibers from Alfa grass and application as reinforcement for polyvinyl alcohol - Ben Cheikh, Salma (2018)
The work reported demonstrates an simple method of extracting cellulose nanofibers (CNF) from cellulose microfibers (CMF) obtained from the plant Stipatenacissima. Here, a method for the production of CNF from CMF extracted from Alfa grass by exfoliation in polyvinyl alcohol (PVA) solution, is demonstrated. The CMF were produced in powder form and exfoliated in PVA aqueous solution to produce composites with 2, 4, 5 and 10 wt-% of CNF. Scanning Electron Microscopy demonstrated exfoliation of CMF, dispersion of the CNF and wetting by the polymer. The composites were characterised by thermogravimetry, differential scanning calorimetry, X-ray diffraction and tensile testing. The addition of CNF to PVA reduced the crystallinity degree of PVA. The large increase of the Young’s modulus from 38 to 113% (relative to pure PVA) for composites with 2 to 10 wt-% of CNF incorporation is consistent with the extensive exfoliation of CMF into CNF and its excellent interface with PVA.